2014
DOI: 10.3389/fnbeh.2014.00246
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment alters protein expression as well as the proteomic response to cocaine in rat nucleus accumbens

Abstract: Prior research demonstrated that environmental enrichment creates individual differences in behavior leading to a protective addiction phenotype in rats. Understanding the mechanisms underlying this phenotype will guide selection of targets for much-needed novel pharmacotherapeutics. The current study investigates differences in proteome expression in the nucleus accumbens of enriched and isolated rats and the proteomic response to cocaine self-administration using a liquid chromatography mass spectrometry (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
5
26
0
Order By: Relevance
“…Further, a recent proteomic study found that the microtubule-associated protein tau was upregulated in EC rats compared to IC rats (Fan et al, 2013a). That paper and two other proteomics papers also identified huntingtin, presenilin 1, tau and amyloid precursor protein as major upstream regulators for environmental enrichment (Fan et al, 2013b; Lichti et al, 2014). These results warrant further investigation of neurodegenerative disorders using the environmental enrichment paradigm.…”
Section: 6 Other Disordersmentioning
confidence: 82%
“…Further, a recent proteomic study found that the microtubule-associated protein tau was upregulated in EC rats compared to IC rats (Fan et al, 2013a). That paper and two other proteomics papers also identified huntingtin, presenilin 1, tau and amyloid precursor protein as major upstream regulators for environmental enrichment (Fan et al, 2013b; Lichti et al, 2014). These results warrant further investigation of neurodegenerative disorders using the environmental enrichment paradigm.…”
Section: 6 Other Disordersmentioning
confidence: 82%
“…The right side was used for protein quantification (Lichti et al, 2014). The RNA was extracted and purified with the RNeasy mini kit (Qiagen, Valencia, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A secondary analysis of our previously published liquid chromatography tandem mass spectrometry (LC-MS/MS) protein data from these same rats (Lichti et al, 2014) was used to corroborate RNA results where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that genes related to memory formation, synaptic plasticity, and protein synthesis may be upregulated by a period of environmental enrichment (Lichti et al, 2014; Novkovic et al, 2015; Sampedro-Piquero et al, 2014) including group 1 metabotropic glutamate receptors (mGluR1/5) (Melendez, Gregory, Bardo, & Kalivas, 2004). Indeed, the role of metabotropic glutamate receptor subtype 5 (mGluR5) in learning and memory is well established; mice lacking mGluR5 show impaired learning on the Morris water maze and contextual fear conditioning tasks (Lu et al, 1997), and the daily application of the mGluR5 antagonist 2-methyl-6-(phenylethyl)pyridine (MPEP) causes impairments in working and reference memory in rats (Manahan-Vaughan & Braunewell, 2005).…”
Section: Introductionmentioning
confidence: 99%